Research on motion characterization of goose neck in narrow space - Zhang, Fu; Sun, Haoxuan; Wang, Jiajia; Wang, Xinyue; Qiu, Yubo; Cui, Xiahua; Ali, Shaukat (Frontiers in Veterinary Science, 2024)
IntroductionInspired by the obstacle avoidance mechanism of goose neck, a theoretical design method of bionic robotic arm was proposed to solve the contradiction between high flexibility and strong bearing capacity in narrow space.MethodsTaking the goose neck as the test object, a narrow space test environment with a width of 10 cm was built, and a 6 × 4 obstacle matrix was set up, to analyze the maximum value of joint angle, motion rate and trajectory in different target areas.ResultsThe test results showed that the goose neck movement has continuity and transmissibility. The overall posture of the goose neck was adjusted through the synergistic movement of the anterior, middle and posterior segments to move toward the target position. The regulating effect of the anterior segment was significantly stronger than that of the middle and posterior segments. Specifically, the anterior segment of goose neck exhibited mostly transverse movement, with significant horizontal regulation; the middle segment of the goose neck was coupled with longitudinal movement, with similar movement ability in all directions, the posterior segment of the goose neck has mostly longitudinal movement, with significant height regulation.ConclusionIn addition, the YOLOv7-pose recognition network was used to recognize goose neck motion pose, which provides a new method for animal behavior research.